Conversion of α-Diazoketones into 1-Bromo-2-alkyl- or 2-arylpent-4-en-2-ols using Tin-Mediated Allylation/Propargylation - Swapan Kumar Biswas; Sipak Joyasawal (SynOpen, 2023)
High-yielding and mild conditions are used to prepare of 1-bromo-2-alkyl- or 2-arylpent-4-en-2-ols/1-bromo-2-alkyl- or 2-arylpent-4-yn-2-ols from α-diazoketones. The reaction involves allylation/propargylation with successive bromide insertion using in situ generated allyltin bromide/or propargyltin bromide from activated tin metal and allyl/or propargyl bromide.